Optimal number and orientation of anterior segment OCT images to measure ocular biometric parameters in angle closure eyes: the Chinese American Eye Study - Shan, Jing; Pardeshi, Anmol; Jiang, Xuejuan; Richter, Grace M; McKean-Cowdin, Roberta; Varma, Rohit; Xu, Benjamin Y (British journal of ophthalmology, 2023)
PurposeTo assess the optimal number and orientation of anterior segment optical coherence tomography (AS-OCT) images for accurately measuring ocular biometric parameters in angle closure eyes.MethodsSubjects with angle closure, defined as >3 quadrants of non-visible pigmented trabecular meshwork on static gonioscopy, were selected from the Chinese American Eye Study. Mean angle opening distance (AOD500) was calculated using four images (0°−180°, 45°−225°, 90°−270° and 135°−315° meridians) from one eye per subject. Ten eyes from each quartile of AOD500 measurements were randomly selected for detailed 32-image analysis of 10 biometric parameters, including AOD500, iris curvature (IC), anterior chamber depth (ACD), lens vault (LV), and anterior chamber area (ACA). Mean and range of measurements from 1, 2, 4, 8 or 16 images were compared with 32-image values for all parameters.Results40 out of 335 eyes with angle closure were selected for 32-image analysis. Deviation from the 32-image mean was between 0.44% and 19.31% with one image, decreasing to 0.08% to 4.21% with two images for all parameters. Deviation from the 32-image range of measurements was between 54.67% to 88.94% with one image, decreasing to <7.00% with eight images for all parameters except ACD and ACA. Orienting the first image analysed along the 25°−205° meridian better approximated the range of measurements when four or fewer images were analysed.ConclusionsSectoral anatomical variations in angle closure eyes are easily misrepresented based on current AS-OCT imaging conventions. A revised multi-image approach can better capture the mean and range of biometric measurements.